Productive parameters in three production models: floor, cage and grazing in layer poultry in Ocaña Norte de Santander - Myriam Quintero MEZA; Katty Andrea Torrado LOBO; Yesenia Picon SANCHEZ; Naudin Alejandro Lugo HURTADO (Revista Brasileira de Saúde e Produção Animal, 2022)
ABSTRACT The objective was to evaluate the three housing systems in laying birds to determine animal welfare and productivity parameters of the Isa Brown line. 135 laying hens distributed in 45 hens were used for each exploitation system; the managed feeding was 114gr/bird/day in the floor and cage systems for the entire trial period, for the grazing system 14 gr less of concentrate were used; the study had a duration of 8 weeks, of which the first was for accustoming and 7 for testing; At the end of each week, 9 eggs were collected to be studied and analyzed in the animal nutrition laboratory, using 3 eggs for each housing system. The information obtained was analyzed using SPSS for each variable. The parameters of production, consumption, feed conversion, and egg weight, were evaluated; where one-factor ANOVA and Tukey HSD test and least significant difference. The percentage production was no significant difference between the three cage floor and grazing production models being (P-Value <0.05), for the food consumption parameter there is a significant difference (P-Value> 0.05) for each housing system (34.54 ± 6.93), also happened with the conversion variable between the floor, cage production models with the grazing one (1.93 ± 0.6), for the egg weight they were similar in all housing systems (61.1 g in cage, 60.8 g in floor and 60.6 g in grazing) where there were no significant differences. In conclusion, birds with a lower housing density allow better behavior, which is an indicator of comfort, generating higher productivity.